Philo of Alexandria An Annotated Bibliography 1997-2006 - Runia, David T. (Vigiliae Christianae, Supplements, 2011)
This volume, prepared with the collaboration of the International Philo Bibliography Project, is the third in a series of annotated bibliographies on the Jewish exegete and philosopher Philo of Alexandria. It contains a listing of all scholarly writings on Philo for the period 1997 to 2006. Readership: The book will be of interest for scholars working in the areas of classicial studies, ancient philosophy Jewish studies, New Testament and Early Church. As a valuable bibliographical resource it will be an essential purchase for all libraries serving scholars in these areas.